Influência da distância no bem estar e qualidade de carne de suínos transportados em Mato Grosso - Ochove, Vivian Christina da Costa (2010)
This study was conducted in a swine slaughterhouse of Mato Grosso to evaluate the influence of the distance between farm and fridge on animal welfare and meat quality. A total of 60 pigs distributed in a completely randomized design and treatments were the distances of 45, 430 and 700km from farm to fridge. Each pig was considered an experimental unit. The parameters of pH postmortem, color, drip loss were used to evaluate the quality of meat and meat determine PSE (pale, soft and exudative) and DFD (dark, firm and dry) as values. Aliquots for determination of blood serum indicators of stress, creatine phosphokinase, lactate dehydrogenase and cortisol were collected. The frequency of mortality was assessed at the landing and the death rate and animal tired. The results showed that the color and drip loss were not significantly affected by the distance between farm and store, as well as pH24 hours postmortem in longissimus dorsi and pH1 and pH24 in the semimembranosus. There were no instances of PSE and DFD meat among the different treatments. The shortest distance greater number of animals while tired, the longest distance between farm and store marked the largest loss by mortality. Thus, we conclude that the shortest distance caused higher levels of cortisol, acute stress characterized as the greatest distance, greater losses through chronic stress and mortality.